2022
DOI: 10.1186/s13014-022-02099-y
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation based on 18F-FDG PET/CT response in definitive chemoradiotherapy of locally advanced esophageal squamous cell carcinoma: a phase III, open-label, randomized, controlled trial (ESO-Shanghai 12)

Abstract: Introduction Definitive chemoradiotherapy has established the standard non-surgical treatment for locally advanced esophageal cancer. The standard dose of 50–50.4 Gy has been established decades ago and been confirmed in modern trials. The theorical advantage of better local control and technical advances for less toxicity have encouraged clinicians for dose escalation investigation. 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) have the potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…At the 2022 American Society for Therapeutic Radiology and Oncology (ASTRO), a multicenter phase III randomized clinical trial (NROG-001) [27] reported that the HD arm (59.4 Gy) did not present significantly prolonged OS (HR = 0.93, P = 0.54) but exhibited improved PFS (29.1 months to 20.0 months, HR = 0.77, P = 0.023) when compared with the SD arm (50.4 Gy) for local advanced thoracic ESCC. The ongoing Chinese ESO-Shanghai 12 study [28] and British SCOPE2 study [29] are making an earnest endeavor to compare the effects of standard-dose and high-dose radiation treatments. The final results of these clinical studies are awaited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 2022 American Society for Therapeutic Radiology and Oncology (ASTRO), a multicenter phase III randomized clinical trial (NROG-001) [27] reported that the HD arm (59.4 Gy) did not present significantly prolonged OS (HR = 0.93, P = 0.54) but exhibited improved PFS (29.1 months to 20.0 months, HR = 0.77, P = 0.023) when compared with the SD arm (50.4 Gy) for local advanced thoracic ESCC. The ongoing Chinese ESO-Shanghai 12 study [28] and British SCOPE2 study [29] are making an earnest endeavor to compare the effects of standard-dose and high-dose radiation treatments. The final results of these clinical studies are awaited.…”
Section: Discussionmentioning
confidence: 99%
“…After Careful examination and discreet exclusion, seven prospective trials [18] [19] [20] [22] [23] [24] [25] were included in the meta-analysis ultimately (Table 1; exclusion reasons were shown in Figure 1), which consisted of6 randomized clinical trials and 1 non-randomized study. The sample size in each study included in the meta-analysis ranged from 28…”
Section: Eligible Studies Descriptionmentioning
confidence: 99%
“…ENI irradiates a bunch of lymph node regions, which may aggravate radiotherapy side effects and deteriorate prognosis for patients, and this may be the reason for invalid beneficial effect from high-dose radiotherapy. Unlike previous prospective studies comparing high-dose to standard dose, the ESO-Shanghai 12 study (35) not only evaluated the prognosis of patients based on PET-CT, but also used involved field irradiation (IFI), which is noteworthy.…”
Section: Evolution Of Dcrt For Inoperable La-esccmentioning
confidence: 99%
“…However, enhancing the precision of forecasts requires the optimization of particular methods and factors (95-97). Data from clinical studies on LA-ESCC are gradually increasing, and more and more studies are beginning to apply PET/CT to assess patient treatment efficacy and to guide treatment decisions based on imaging response (35,98,99). There are even new PET imaging techniques that can detect tumor PD-L1, allowing noninvasive, real-time monitoring of changes in a patient's PD-L1 status (100).…”
Section: Patient Selection and Predictive Markersmentioning
confidence: 99%